Mamlakat INNOVATIVE TECHNOLOGIES OF TEACHING ENGLISH LANGUAGE: INNOVATIVE TECHNOLOGIES OF TEACHING ENGLISH LANGUAGE - Ismoilova, Mamlakat (Журнал иностранных языков и лингвистики, 2022)
This article analyses the innovative and quite interesting methods we have in teaching English language. The teaching methodology can be, but teaching must be leaner’s centered. However, this article scrutinizes the difference between traditional and practical teaching and thereafter learning. This treatise practically examines that how learners are being affected by the traditional methods of teaching as well, besides it has portrayed that how learners expect teaching and learning process.